Is there evidence for a trade-off between sperm competition traits and forelimb musculature in the western grey kangaroo? - Martin, M.; Bateman, Bill; Auckland, C.; Miller, D.; Warburton, N.; Barnes, A.; Fleming, P. (Wiley-Blackwell, 2018)
© 2017 The Linnean Society of London. Males may use tactics before, during and after mating to increase their reproductive success. With finite energy resources available, theory predicts that there should be a trade-off between investment in pre-copulatory traits (e.g. body size, armaments) and post-copulatory traits (e.g. testes size, spermatogenic efficiency). Western grey kangaroos (Macropus fuliginosus) are found in large, labile mixed-sex groups, in which the males show a dominance hierarchy. Males show indeterminate growth, and will reach up to six times the body mass of females. While the largest males use their size as a reproductive advantage, forelimb musculature further aids male-male contest, female attraction and/or female coercion. Under a trade-off scenario, we therefore predicted that larger, more muscular males would show less investment in sperm competitive traits. Consistent with this prediction, more muscular males showed decreased spermatozoa velocity. However, muscularity was also positively correlated with mass of two pairs of bulbourethral accessory glands, as well as mass of the penis and its muscles of erection. Seasonal changes in muscularity and accessory gland masses were also evident. Male kangaroos therefore invest in multiple reproductive traits on which selection can work.